«…This Phenomenon, Which is None too Happily Designated as “Empathy”». Martin Heidegger’s Critique of Empathy - Brencio, Francesca (Bollettino Filosofico, 2022)
Martin Heidegger offers an original and valuable contribution to the debate around empathy. In what follows I am going to provide an account of his critique of empathy in terms of mental transposition or projection, drawing on the resources from the early Freiburg courses, Being and Time and the Zollikon Seminars. This critique of the notion of empathy is rooted in an account of subjectivity conceived not as an isolated self, but rather as a Dasein ecstatically open, embedded in the world, and grounded in the ontological structure of Mitsein, and, more in general, in Heidegger’s critique of western metaphysics, especially the notion of the isolated ego as the foundational point of western philosophy. Finally, I will show how the intersubjective nature of Dasein as Miteinandersein is related to the issue of authenticity and has important consequences in our social life. Keywords: Empathy, Ethics, Heidegger, Intersubjectivity, Medicine